Toward Highly Stable Anode for Secondary Batteries: Employing TiO2 Shell as Elastic Buffering Marix for FeOx Nanoparticles. Issue 11 (20th January 2022) - Luo, Rui; Hu, Xin; Zhang, Nanxiang; Li, Li; Wu, Feng; Chen, Renjie
Abstract: Transition metal oxides are considered promising anode materials for next‐generation lithium‐ion and sodium‐ion batteries (LIBs and SIBs) because of their high theoretical capacities; however, their practical application is limited by the detrimental large volume expansion that occurs upon cycling. In this work, a rationally designed TiO2 @Fe@FeO x nanocomposite encapsulated by a TiO2 shell with unique core–shell structure is synthesized and exhibits outstanding electrochemical performance as an anode in LIBs and SIBs. The nanocomposite exhibits a reversible capacity of 619.2 mAh g −1 at 1 A g −1 with a coulombic efficiency over 99.5% after 1000 cycles when used as a LIB anode. The nanocomposite also exhibits superior sodium storage performance (267 mAh g −1 at 50 mA g −1, capacity retention of 65.4% after 1000 cycles at 200 mA g −1 ). The TiO2 shell serves as a strong conformal layer and soft matrix that can tolerate the volume expansion and maintain the structural integrity of the anode during discharging and charging. Moreover, the open active diffusion channels of the shell contribute to high ion diffusivity and improved ionic, and electronic diffusion. These findings indicate that adoption of TiO2 coating is an effective strategy to optimize the electrochemical performance of transition metal oxide anode materials. Abstract : A rationally designed TiO2 @Fe@FeO x nanocomposite encapsulated by an amorphous TiO2 shell is explored. The amorphous conformal TiO2 coating layer serves as a strong conformal layer and soft matrix to tolerate the volume expansion and maintain the overall structural integrity. In addition, the open active diffusion channels of TiO2 shell contribute to high ion diffusivity and improved ionic and electronic diffusion.